2021
DOI: 10.1261/rna.078933.121
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and splicing dynamics during early Drosophila development

Abstract: Widespread co-transcriptional splicing has been demonstrated from yeast to human. However, most studies to date addressing the kinetics of splicing relative to transcription used either Saccharomyces cerevisiae or metazoan cultured cell lines. Here, we adapted native elongating transcript sequencing technology (NET-seq) to measure co-transcriptional splicing dynamics during the early developmental stages of Drosophila melanogaster embryos. Our results reveal the position of RNA polymerase II (Pol II) when both… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 111 publications
(239 reference statements)
0
14
0
Order By: Relevance
“…We assume that introns are co-transcriptionally spliced and rapidly degraded. In support of this, NET-seq data suggests that >95% of splicing events are co-transcriptional in the Drosophila embryo [29] and modelling of metabolic labelling and sequencing data from Drosophila S2 cells revealed that the median half-life of introns is 2 minutes [30].…”
Section: Gaussian Process Regression Provides Estimates Of Transcript...mentioning
confidence: 78%
“…We assume that introns are co-transcriptionally spliced and rapidly degraded. In support of this, NET-seq data suggests that >95% of splicing events are co-transcriptional in the Drosophila embryo [29] and modelling of metabolic labelling and sequencing data from Drosophila S2 cells revealed that the median half-life of introns is 2 minutes [30].…”
Section: Gaussian Process Regression Provides Estimates Of Transcript...mentioning
confidence: 78%
“…We assume that introns are co-transcriptionally spliced and rapidly degraded. In support of this, NET-seq data suggests that >95% of splicing events are co-transcriptional in the Drosophila embryo [29] and modelling of metabolic labelling and sequencing data from Drosophila S2 cells revealed that the median half-life of introns is 2 min [30].…”
Section: Resultsmentioning
confidence: 98%
“…We assume that introns are spliced at the same rate for each mRNA, consistent with evidence from S2 cells that introns from the same mRNA tend to have similar splicing rates [30]. We normalised the read counts by the intron lengths so that the S parameter has comparable meaning for each mRNA, but allow it to differ from mRNA-to-mRNA to account for variation in splicing rates across genes [29] and also differences due to alternative splicing of different transcripts. For transcripts we used TPM units which normalises for transcript length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed the decetion of splicing intermediates, such as exon 3ʹ-end and intron lariats, but prevented the analysis of promoter-proximal stalling. It thus seems that the two approaches can capture complementary information [ 40 ].
Figure 1.
…”
Section: Resultsmentioning
confidence: 99%